Reduced Expression of GABAA Receptor Alpha2 Subunit Is Associated With Disinhibition of DYT-THAP1 Dystonia Patient-Derived Striatal Medium Spiny Neurons - Staege, Selma; Kutschenko, Anna; Baumann, Hauke; Glaß, Hannes; Henkel, Lisa; Gschwendtberger, Thomas; Kalmbach, Norman; Klietz, Martin; Hermann, Andreas; Lohmann, Katja; Seibler, Philip; Wegner, Florian (Frontiers in Cell and Developmental Biology, 2021)
DYT-THAP1 dystonia (formerly DYT6) is an adolescent-onset dystonia characterized by involuntary muscle contractions usually involving the upper body. It is caused by mutations in the gene THAP1 encoding for the transcription factor Thanatos-associated protein (THAP) domain containing apoptosis-associated protein 1 and inherited in an autosomal-dominant manner with reduced penetrance. Alterations in the development of striatal neuronal projections and synaptic function are known from transgenic mice models. To investigate pathogenetic mechanisms, human induced pluripotent stem cell (iPSC)-derived medium spiny neurons (MSNs) from two patients and one family member with reduced penetrance carrying a mutation in the gene THAP1 (c.474delA and c.38G > A) were functionally characterized in comparison to healthy controls. Calcium imaging and quantitative PCR analysis revealed significantly lower Ca2+ amplitudes upon GABA applications and a marked downregulation of the gene encoding the GABAA receptor alpha2 subunit in THAP1 MSNs indicating a decreased GABAergic transmission. Whole-cell patch-clamp recordings showed a significantly lower frequency of miniature postsynaptic currents (mPSCs), whereas the frequency of spontaneous action potentials (APs) was elevated in THAP1 MSNs suggesting that decreased synaptic activity might have resulted in enhanced generation of APs. Our molecular and functional data indicate that a reduced expression of GABAA receptor alpha2 subunit could eventually lead to limited GABAergic synaptic transmission, neuronal disinhibition, and hyperexcitability of THAP1 MSNs. These data give pathophysiological insight and may contribute to the development of novel treatment strategies for DYT-THAP1 dystonia.